COMPUTER MODELS FOR STUDYING THE PROCESS OF DRYING GRAPES (Academicia Globe: Inderscience Research, 2022)
It is known that, if the moisture content of the material is not high, moisture moves mainly in the form of steam, i.e. drying occurs due to molecular vapor transfer, and at high humidity, moisture partially moves in the form of a liquid, while the evaporation zone approaches the surface of the material, the surface of the dried material increases, and therefore the evaporation of moisture increases [1, 2].